2023
DOI: 10.3390/antiox12020415
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Role of Vitamins and Minerals in Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is the most common type of dementia that affects millions of individuals worldwide. It is an irreversible neurodegenerative disorder that is characterized by memory loss, impaired learning and thinking, and difficulty in performing regular daily activities. Despite nearly two decades of collective efforts to develop novel medications that can prevent or halt the disease progression, we remain faced with only a few options with limited effectiveness. There has been a recent growth of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 292 publications
0
26
0
Order By: Relevance
“…Recent studies have shown that NR4A2 activation enhances long-term memory in young mice and ameliorates age-related memory impairments in old mice ( 36 ). Several studies have also suggested that water-soluble vitamins (C, E, and Bs) may affect cognitive performance by reducing reactive oxygen species generation and proinflammatory mediators such as NLRP3 inflammasome ( 37 ). Retinoic acid, the active form of vitamin A, is essential for regulating synaptic plasticity in regions of the brain involved in memory and learning ( 38 ).…”
Section: Resultsmentioning
confidence: 99%

Adipose tissue coregulates cognitive function

Oliveras-Cañellas,
Castells-Nobau,
de la Vega-Correa
et al. 2023
Sci. Adv.
“…Recent studies have shown that NR4A2 activation enhances long-term memory in young mice and ameliorates age-related memory impairments in old mice ( 36 ). Several studies have also suggested that water-soluble vitamins (C, E, and Bs) may affect cognitive performance by reducing reactive oxygen species generation and proinflammatory mediators such as NLRP3 inflammasome ( 37 ). Retinoic acid, the active form of vitamin A, is essential for regulating synaptic plasticity in regions of the brain involved in memory and learning ( 38 ).…”
Section: Resultsmentioning
confidence: 99%

Adipose tissue coregulates cognitive function

Oliveras-Cañellas,
Castells-Nobau,
de la Vega-Correa
et al. 2023
Sci. Adv.
“…The pathways from diet to dementia are diverse and likely include both direct effects of microand macro-nutrients on brain health and indirect effects mediated through metabolic, immune, and vascular health. 42 The systemic aging processes captured by DunedinPACE may relate primarily to the indirect pathways. The large unexplained fraction of the dietdementia association may therefore reflect, in part, direct effects of nutrients on brain aging.…”
Section: Discussionmentioning
confidence: 99%
“…43 Nutrients play critical roles in neurotransmission, synaptic functioning, brain vasculature, and adult neurogenesis; eg, omega-3 fatty acids are major components if neuronal membranes. 42,44,45 Some nutrients, such as polyphenols or vitamin A, also have anti-amyloid and anti-tau properties. 34,42,46,47 While there are associations of nutrients with brain structure and white matter integrity phenotypes, 36,46,48 these features of brain aging may also have connections with indirect pathways.…”
Section: Discussionmentioning
confidence: 99%
“…172 Many studies have demonstrated that VE can prevent neurodegenerative disorders such as Alzheimer's disease (AD) and Parkinson's disease (PD) can both be prevented by VE. 173,174 Mounting evidence suggests that patients with autism have low methylation ability and increased production of reactive oxygen species (ROS). In a postmortem study of brain tissues, patients with autism reported higher levels of oxidative stress biomarkers than healthy controls.…”
Section: Vitamin Ementioning
confidence: 99%